2004
DOI: 10.1002/ejic.200400423
|View full text |Cite
|
Sign up to set email alerts
|

Cocondensation Reactions of Five‐Membered Heterocycles with Lithium Atoms at 77 K

Abstract: Lithium atoms were cocondensed with eight aromatic five‐membered heterocycles in the presence of THF at 77 K. In the case of the oxygen‐ and sulfur‐containing heterocycles (furans and thiophenes), the reaction resulted in C−H bond activation and led to the corresponding aryllithium compound. The other heterocycles (pyrroles) failed to react with lithium atoms in the presence of THF. A special case was found when oxazole was reacted under these cocondensation conditions; here a dilithiated product was obtained.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Previous research in this area showed that five-membered heterocycles react with lithium atoms in the presence of THF under cocondensation conditions [8]. The isolated products were identified as lithiated aromatic compounds.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous research in this area showed that five-membered heterocycles react with lithium atoms in the presence of THF under cocondensation conditions [8]. The isolated products were identified as lithiated aromatic compounds.…”
Section: Discussionmentioning
confidence: 98%
“…No reaction [8] No reaction (15), this Ca-O interaction is lost (d CaO : 326.2 pm). This is due to the coordination number 6 at the calcium centre; now the intramolecular donor furyl cannot compete against the solvent molecules.…”
Section: N No Reactionmentioning
confidence: 95%
See 3 more Smart Citations